House values and proximity to a landfill in South Africa - Du Preez, Mario; Balcilar, Mehmet; Razak, Aarifah; Koch, Steven F.; Gupta, Rangan (American Real Estate Society 314 Sirrine Hall Clemson SC 29634-1343, 2016)
In this paper, we explore the relation between proximity to a landfill and housing values in the Nelson Mandela Bay Metropole (NMBM), South Africa, extending the research by Du Preez and Lottering (2009), who found a negative relation. The results corroborate the findings of Du Preez and Lottering and indicate that the negative relation is most pronounced at the lowest and highest housing values. Specifically, house values increase by an average of ZAR19.0 or US$1.81 (0.2%) for every 100 meters away from the landfill. For the lowest 5% of house values, this increase is only 0.11% while at the top 5%, house values increase by 0.21%. This clearly demonstrates that "wealthier" owners stand to gain more by being situated further from landfills than "poorer" owners. © 2016, American Real Estate Society. All rights reserved.